Layout and Thermal Analysis of Power Devices Using a PC/XC - J. N. Avaritsiotis; G. Eleftheriades (Active and Passive Electronic Components)
Thermal analysis during the design process is an essential step towards the achievement of high reliability in modern high density hybrid and integrated circuits. Thermal analysis is also essential for modern, high density PCBs. Traditionally, a solution of the thermal problem is obtained by either the method of finite differences or the method of finite elements. Both methods, however, require a fine 3-D partition of the substrate, leading to large systems of linear equations the solution of which demands substantial computing power provided by number crunching machines and/or powerful computer work-stations.